1991
DOI: 10.1111/j.1476-5381.1991.tb12195.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of captopril on membrane current and contraction in single ventricular myocytes from guinea‐pig

Abstract: 1Single guinea-pig ventricular myocytes were voltage-clamped and cell length was measured with a photodiode array. 2 Captopril (1 x 10-5M) reduced both peak early current and active shortening in response to a depolarizing clamp pulse along a similar time course. 3 From a holding potential of around -45 mV peak early inward current was reduced by 37 + 9% (P < 0.001) on exposure to captopril. The early current-voltage relationship was shifted outwards by captopril indicating a reduction in membrane conductanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
1
2
2
Order By: Relevance
“…Therefore, it may be argued that captopril’s negative effect on I Ca,L is not through the Ang II system or PI3-kinase signaling. In support of our data, earlier reports also showed that treatment with captopril decreased the I Ca,L level of normal ventricular myocytes (Bryant et al 1991), as well as reduced calcium influx without affecting the resting baseline Ca 2+ concentration of WKY rats (Wang et al 1996). …”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it may be argued that captopril’s negative effect on I Ca,L is not through the Ang II system or PI3-kinase signaling. In support of our data, earlier reports also showed that treatment with captopril decreased the I Ca,L level of normal ventricular myocytes (Bryant et al 1991), as well as reduced calcium influx without affecting the resting baseline Ca 2+ concentration of WKY rats (Wang et al 1996). …”
Section: Discussionsupporting
confidence: 91%
“…Under these conditions a concentration of lisinopril (10 LM), which reduced the developed contractile force by almost 50%, had no effect on the amplitude or the voltage-dependent properties of the ICa,L. Therefore, and in contrast to what has been previously described with captopril (Bryant et al, 1991), the present experiments demonstrated that the negative inotropic effect of lisinopril cannot be explained through a decrease in Ca2" entry via L-type channels.…”
Section: Discussioncontrasting
confidence: 66%
“…However, lisinopril had no effect on atrial rate and sinus node recovery time, which suggested that it does not exert a direct inhibition of the sinus node function. Captopril also produced a negative inotropic effect in guinea-pig isolated hearts (Walker et al, 1988) and this effect was attributed to an inhibition of ICaL (Bryant et al, 1991). However, in the present experiments the decrease in contractile force appeared at concentrations at which lisinopril had no effect on the duration of the cardiac action potentials.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Furthermore, it was demonstrated that these inhibitory effects of captopril and enalaprilat on Ca2+ influx in VSMC were paralleled by a decreased 268 Zhu/Tepel/Neusser/Zidek Angiotensin-Converting Enzyme Inhibitors and Cytosolic Calcium contractile response to Ang II [23], This study also showed that the attenuation of the Ang II response is due to an inhibition of transplasma membrane Ca2+ influx. Interestingly, similar effects of captopril have also been observed in ventricular myocytes, indicating that Ca2+ influx through L-type channels as well as contraction is inhibited by captopril [24], From these results several questions arose. First, is ago nist-induced Ca2+ influx inhibited similarly by different ACE inhibitors?…”
Section: Discussionmentioning
confidence: 93%